Establishment an empirical relationship equation of magnitude conversion specific for Malaysia - Gaddafi, Ismaili; Taksiah, A. Majid (2019)
This paper presents the results of the establishment an empirical relationship equation of magnitude conversion specific for Malaysia. The data for this study is taken from the earthquake catalogue and that is from Incorporated Research Institutions for Seismology (IRIS), National Earthquake Information Centre (NEIC)-U.S. Geological Survey (USGS), European-Mediterranean Seismological Centre (EMSC) and Malaysian Meteorological Service (MMS) within the latitude of 9 North and-3 South, and longitude of 122 East and 95 West from 1 January 1900 until 31 December 2006. There are two empirical relationship equation will be developed for Malaysia through regression method and there are empirical relationship equation of surface wave magnitude, M s constructed with records that have both surface wave magnitude, M s and body wave magnitude, m b and empirical relationship equation of moment magnitude, M w constructed with records that have both moment magnitude, M w and surface wave magnitude, M s